Análise espaço temporal dos componentes do balanço de radiação, energia e evapotranspiração, usando técnicas de sensoriamento remoto em áreas irrigadas do projeto Jaíba/MG - Veloso, Gabriel Alves (2014)
The present search aims to analyze the components of radiation balance, energy balance and evapotranspiration in irrigated areas of Jaíba Project and surrounding areas. The study area is located in the North of Minas Gerais, in the municipalities of Jaíba and Matias Cardoso, in the right bank of São Francisco River and left bank of Verde Grande River, in zone 23, between the UTM coordinates of 595.204 and 626.309 mE and 8.308.401 and 8.341.257 mN. It were used five images of the Landsat 5 satellite, TM sensor, orbit 219 point 70, obtained in the days January 31st (JD 31), April 21st (JD 111), June 24th (JD 175), July 10th (JD 191) and September 12th (JD 255) in the year of 2011. The components estimate of radiation balance, energy balance and daily evapotranspiration were obtained through the SEBAL algorithm (Surface Energy Balance Algorithm for Land). The SEBAL is constituted of many steps, which include radiometric calibration, computation of reflectance, surface albedo, vegetation indices (NDVI, SAVI, LAI), emissivity, surface temperature, net radiation flux, soil heat flux (G), sensible heat flux (H), latent heat flux (λET) and evapotranspiration. For obtainment of those parameters, it was used data from meteorological station located within the Landsat scene. It were obtained average values of surface albedo in the order of 15%, 17%, 17%, 18% e 21% in irrigated areas in the days JD 31, JD 111, JD 175, JD 191 and JD 255, respectively; average values of net radiation flux in the order of 689,03 W/m-2, 592,51 W/m-2, 447,28 W/m-2, 445,28 W/m-2 and 562,87 W/m-2 for the days JD 31, JD 111, JD 175, JD 191 and JD 255 respectively; and average values for 24-hour evapotranspiration of 6,85 mm.day-1, 4,0 mm.day-1, 2,6 mm.day-1, 2,2 mm.day-1 and 3,4 mm.day-1 for the days JD 31, JD 111, JD 175, JD 191 and JD 255 respectively. It was observed that the components of radiation balance, energy balance and evapotranspiration presented variation in the analyzed period due to the quantity of available radiation for each day and deciduousness of deciduous seasonal forest. The technique used has demonstrated to be efficient in analyzes of the components studied, being the SEBAL an important tool for environmental analyzes and water resources management.